PENGARUH UKURAN KANTOR AKUNTAN PUBLIK DAN INDEPENDENSI KOMITE AUDIT TERHADAP KOEFISIEN RESPON LABA - Barqy Cahya Muhammad; Sugeng Pamudji (Diponegoro Journal of Accounting, 2014)
This research aims to determine the effects brought by the qualification of  public accountant office and independent audit committee to earnings response coefficient. Earnings response coefficient is market reactions towards new information issued by a corporation. In this research earnings response coefficient is production of profit quality. The variable of the public accountant office and the independent audit committee quality is considered effecting value of the profit coefficient profit.            This research is made using method of purposive sampling in selecting samples. Purposive sample is a method used in selecting samples based on several specific criteria, some of which are; samples are manufacturing corporations which are listed in the Indonesian Stock Exchange and actively selling stocks during the period of 2009-2011, whose published financial report and annual report, and 194 corporations with insufficient data sample which 32 of them are outlier data. Research is made using quantitative method, and analyzed with regression analyzing technique, and hypothesis testing made using coefficient determination testing, ‘f’ testing and ‘t’ testing.            The research resulting that factor which has significant influence to earnings response coefficient is only the qualification of the public accountant, Independent audit committee gives positive effect to the coefficient profit response, but insignificant.